TBASCEM - Tight Bounds with Arrival and Service Curve Estimation by Measurements - Funda, Christoph; Herpel, Thomas; German, Reinhard; Hielscher, Kai-Steffen (ICPE 2024 - Proceedings of the 15th ACM/SPEC International Conference on Performance Engineering, 2024)
This paper aims to solve the challenge of quantifying the performance of Hardware-in-the-Loop (HIL) computer systems used for data re-injection. The system can be represented as a multiple queue and server system that operates on a First-In, First-Out (FIFO) basis. The task at hand involves establishing tight bounds on end-to-end delay and system backlog. This is necessary to optimise buffer and pre-buffer time configurations. Network Calculus (NC) is chosen as the basic analytical framework to achieve this. In the literature, there are different techniques for estimating arrival and service curves from measurement data, which can be used for NC calculations. We have selected four of these methods to be applied to datasets of industrial Timestamp Logging (TL). The problem arises because these conventional methods often produce bounds that are much larger (by a factor of 1000 or more) than the measured maximum values, resulting in inefficient design of HIL system parameters and inefficient resource usage. The proposed approach, called TBASCEM, introduces a reverse engineering approach based on linear NC equations for estimating the parameters of arrival and service curves. By imposing constraints on the equation variables and employing non-linear optimization, TBASCEM searches for a burst parameter estimation which derives tight global delay bounds. In addition, TBASCEM simplifies the run-time measurement process, supporting real-time data acquisition to evaluate and optimise HIL system performance, and enhancing observability to adapt the HIL configuration to new sensor data. The benefits of TBASCEM are clearly that it enables an efficient performance logging of arrival and service curve parameters and with deriving tighter bounds in HIL systems, compared to evaluated state-of-the-art methods, making TBASCEM an invaluable tool for optimising and monitoring streaming applications in non-hard-real-time environments.
CRIS-Team Scopus Importer:2024-05-31
Keywords: Arrival and Service Curve Estimation; Hardware-in-the-loop Test System; Network Calculus; Performance Evaluation and Monitoring; Streaming System